Plant factory : an indoor vertical farming system for efficient quality food production - Kozai, Toyoki, 1943-; Niu, Genhua; Takagaki, Michiko (Amsterdam : Academic Press, 2019)
Plant Factory: An Indoor Vertical Faming System of Efficient Quality Food Production presents a comprehensive look at the implementation of plant factory (PF) practices to yield food crops for both improved food security and environmental sustainability. Now in its second edition, the book has been fully revised and updated to include the latest advances in PF technologies. Edited and authored by leading experts in PF and controlled environment agriculture (CEA), the book is divided into four sections, each focused on a key element of successful PF: Section 1: Overview and Concept of Closed Plant Production Systems (CPPS); Section 2: Basics of Physics and PHysiology - Environments and Their Effects; Section 3: System Design, Construction, Cultivation, and Management; and Section 4: Plant Factories in Operation.--COVER
Pt. 1. Overview and concept of closed plant production system (CPPS) -- Introduction -- Role of the plant factory with artificial lighting (PFAL) in urban areas -- PFAL business and R&D in Asia and North America : Status and perspectives -- Vertical faming in Europe : Present status and outlook -- Plant factory as a resource-efficient closed plant production system -- Micro- and mini-PFALs for improving the quality of life in urban areas -- Rooftop plant production systems in urban areas -- Pt. 2. Basics of physics and physiology - Environments and their effects -- Light sources -- Plant responses to light -- LED advancements for plant-factory artificial lighting -- Physical environmental factors and their properties -- Photosynthesis and respiration -- Growth, development, transpiration, and translocation as affected by abiotic environmental factors -- Nutrition and nutrient uptake in soilless culture systems -- Tipburn -- Functional components in leafy vegetables -- Medicinal components -- Production of pharmaceuticals in a specially designed plant factory -- Pt. 3. System design, construction, cultivation and management -- Plant production process, floor plan, and layout of PFAL -- Hydroponic systems -- Seeding, seedling production and transplanting -- Transplant production in closed systems -- Photoautotrophic micropropagation -- Biological factor management -- Design and management of PFALs -- Automated technology in plant factories with artificial lighting -- Life cycle assessment -- Education, training, and business workshops and forums on plant factories -- Pt. 4. PFALs in operation and its perspectives -- Selected PFALs in the United States, the Netherlands, and China -- Selected PFALs in Japan -- Representative plant factories in Taiwan -- Challenges for the next-generation PFALs -- Conclusions : Resource-saving and resource-consuming characteristics of PFALs
BIBINDX
Keywords: Artificial light gardening; Food crops -- Harvesting; Sustainable agriculture; Crops -- Technological innovations; Electronic books